A Witch Alone - Warburton, Ruth
Where do you go when your heart has been ripped out? For Anna there is only one answer; into her past, where the truth about her mother, her power, and her real identity lie hidden. Anna is in crisis, and as the clouds around her gather, Anna is torn between friends, family, and rival tribes of witches
Keywords: English - Fiction